Meta-Analysis: Application of Health Belief Model to Breast Self-Examination (BSE) - Desi Syahbaniar; Dian Asih Ning Utami (Journal of Health Promotion and Behavior, 2022)
Background: Breast cancer is a type of non-communicable disease characterized by the appearance of abnormal cells in the breast. Breast self-examination (BSE) is one method of early detection of breast cancer. Health belief model is a health behavior that can predict women's interest in doing BSE. This study aimed to estimate the effect of the health belief model on the practice of BSE with a meta-analysis.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2015-2022 using databases from PubMed, Google Scholar and Scopus. Based on the database, there were 9 articles that met the inclusion criteria. The analysis was carried out using Revman 5.3 software.Results: As many as 9 articles spread across 2 continents, namely Asia and North America. 8 main studies from Asia, 3 from Turkey, 2 from Iraq, 1 from Yemen, 1 from Iran, and 1 from Indonesia. One major study from North America, namely Mexico, reviewed in the meta-analysis showed that perceived benefits were strong (aOR= 1.03; 95%CI= 0.96 to 1.11; p= 0.440; I2=79%).Conclusion: The perceived benefits were not statistically significant in predicting the practice of BSE in women.Keywords: health belief model, perceived benefit, BSECorrespondence:Desi Syahbaniar. Study Program of Medical Record, Jember State Polytechnic, East Java. Jl. Mastrip, Krajan Timur, Sumbersari, Jember, East Java, 68121. Email: desiniar15@gmail.com. Mobile: +6287708465646Journal of Health Promotion and Behavior (2022), 07(01): 1-8DOI: https://doi.org/10.26911/thejhpb.2021.07.01.01